2013
DOI: 10.1038/ismej.2013.110
|View full text |Cite
|
Sign up to set email alerts
|

Previously unknown and highly divergent ssDNA viruses populate the oceans

Abstract: Single-stranded DNA (ssDNA) viruses are economically important pathogens of plants and animals, and are widespread in oceans; yet, the diversity and evolutionary relationships among marine ssDNA viruses remain largely unknown. Here we present the results from a metagenomic study of composite samples from temperate (Saanich Inlet, 11 samples; Strait of Georgia, 85 samples) and subtropical (46 samples, Gulf of Mexico) seawater. Most sequences (84%) had no evident similarity to sequenced viruses. In total, 608 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
164
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 40 publications
(45 reference statements)
4
164
0
Order By: Relevance
“…A recent comprehensive metagenomic analysis of thousands of diverse samples has led to the discovery of approximately 125,000 new viral genomes and a 16-fold increase in the number of identified viral genes 24 . Similarly, as technology advances, it is becoming clear that ssDNA and RNA viruses in marine and other ecosystems are far more diverse than currently characterized viruses; however, these new viruses remain understudied despite their ecological importance 11,[25][26][27][28][29][30][31] . Many ssDNA viruses identified in metagenomic data encode an evolutionarily conserved replication-associated protein (Rep), whereas the number, orientation and evolutionary origin of other genes are highly variable in these circular Rep-encoding ssDNA viruses (CRESS-DNA viruses) 32 .…”
Section: Virus Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comprehensive metagenomic analysis of thousands of diverse samples has led to the discovery of approximately 125,000 new viral genomes and a 16-fold increase in the number of identified viral genes 24 . Similarly, as technology advances, it is becoming clear that ssDNA and RNA viruses in marine and other ecosystems are far more diverse than currently characterized viruses; however, these new viruses remain understudied despite their ecological importance 11,[25][26][27][28][29][30][31] . Many ssDNA viruses identified in metagenomic data encode an evolutionarily conserved replication-associated protein (Rep), whereas the number, orientation and evolutionary origin of other genes are highly variable in these circular Rep-encoding ssDNA viruses (CRESS-DNA viruses) 32 .…”
Section: Virus Diversitymentioning
confidence: 99%
“…However, these sequenced viruses lack information about their hosts and other biological properties that would guide their assignment into species and genera in the family 10 . Indeed, vast numbers of complete, or nearly complete, genome sequences have been assembled and characterized from metagenomic data for viruses with small [11][12][13][14] , medium [15][16][17][18] and even large 19,20 genomes. The identification of entirely new groups of viruses from such analyses emphasizes the power of metagenomic approaches in discovering viruses, some of which could have key functions in the regulation of ecosystems, whereas others could coexist with their hosts without causing recognizable disease or may even be mutualists 7 .…”
mentioning
confidence: 99%
“…Phage phiX174 was the very first whole genome to be sequenced and the first virus for which the complete structure was determined. While phages similar to phiX174 have been reported to be abundant in the environment, they are challenging to isolate (25). We believe that isolation and characterization of additional Microviridae phages are key to a better understanding of the evolution of members of this phage family in their natural environment.…”
Section: Figmentioning
confidence: 99%
“…The first approach involves replication of viruses in a chemostat with and without different selective pressures for many generations (15)(16)(17)(18)(19)(20)(21)(22)(23). The second approach is based on isolating and sequencing novel members of the virus family (24) and surveying environmental sequences (25). A recent review on evolutionary studies showed that Microviridae phages undergo parallel evolution, meaning that a common ancestor evolved the same molecular substitutions even when different selective pressures were used (26).…”
mentioning
confidence: 99%
“…ssDNA viruses include a subgroup which possess circular genomes, and a particular replication initiation gene, rep. These are therefore called Circular Rep-Encoding ssDNA (CRESS-DNA) viruses (Rosario et al, 2009;Delwart and Li, 2012;Labonté and Suttle, 2013;Simmonds et al, 2017). These include the Geminiviridae, Nanoviridae, Circoviridae, and Genomoviridae, which employ rolling-circle replication (RCR), facilitated by the Rep protein (Rosario et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%